THE INFLUENCE OF SUSTAINABLE ECOTOURISM INFRASTRUCTURE ON LOCAL GOVERNMENT POLICY IN THE NATIONAL STRATEGIC TOURISM AREA OF YOGYAKARTA - Muhamad, Muhamad; AB, Ahmad; Supriyadi, Hamam (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Effective policymaking in tourism should reflect on-the-ground realities. This study examines the impact of sustainable ecotourism infrastructure on local government policies in Yogyakarta, assessing whether existing policies align with empirical field evidence. Additionally, it introduces a structured methodology for evaluating sustainability in tourism development. This study employs a mixed-method approach, combining Partial Least Squares-Structural Equation Modeling (PLS-SEM) for quantitative analysis with qualitative descriptive analysis. A purposive sampling method was used to select 100 respondents, including academicians, destination managers, local government officials, and tourism industry specialists. The analysis covers the outer model, inner model, and hypothesis testing to explore the relationship between sustainable infrastructure indicators and policy development. Findings reveal a significant relationship between sustainable tourism infrastructure and government policies, particularly in environmental sensitivity and waste management. However, water resource management has a minimal impact on policy decisions. This suggests that while sustainability concerns shape policymaking, some infrastructure aspects remain underprioritized. This study contributes to sustainable tourism research by introducing a 12-indicator ecological infrastructure assessment aligned with Global Sustainable Tourism Council (GSTC) standards. It also validates the Penta Helix model’s effectiveness in integrating multiple stakeholders into policy development. The study highlights the need for improved water management strategies, better environmental monitoring, and stronger policy frameworks. Future research should expand geographic scope and stakeholder representation to enhance policy recommendations for sustainable tourism governance.